The trip to Greece [videorecording (DVD)] - Winterbottom, Michael; Winterbottom, Michael; Winterbottom, Michael; Coogan, Steve; Brydon, Rob, 1965-; Towns, Michael (IFC Films, 2020)
Two friends travel to different towns in Greece together, enjoying the different types of cuisine that each has to offer.